Interpendensi Masyarakat dan Pewarisan Hak Milik Atas Tanah Adat di Amfoang-Timor Barat - Tanaos, Jonsilas; Din, Teresia (Fundamental: Jurnal Ilmiah Hukum, 2025)
Abstract The interdependence between humans in living in society shows that humans, apart from being individual beings, are also social beings who are always in contact with other humans, which Aristotle known as zoon politicon. To maintain harmonious relationships and continuity of life, one of the most important elements is awareness of community law as an important basis for organizing life together in various aspects of life, especially those related to the status of ownership of land rights, including customary land. The desire to own, control land objects and enjoy the fruits of the land for a relatively long time and maintain ownership rights over the land until passing it on to heirs is regulated in accordance with the provisions of local customary law which have long been guided and practiced by the community. The legal rules adopted by the Amfoang indigenous community clearly regulated land ownership rights long before the enactment of Law Number 5 of 1960 concerning Basic Agrarian Regulations. However, the interdependence of the community, which is characteristic of the Amfoang indigenous community, ultimately creates the potential for land disputes within the community. This is not because of the weakness of the legal system adopted but because of the legal awareness and legal knowledge of the community as well as the unity of various elements which is the cause of the weakening of the status of land ownership rights in the Amfoang community.